2020
DOI: 10.3390/ma13194452
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of γ′ Precipitates, Carbides and Nano-Borides in Heat-Treated Ni-Based Superalloy Using SEM, STEM-EDX, and HRSTEM

Abstract: The microstructure of a René 108 Ni-based superalloy was systematically investigated by X-ray diffraction, light microscopy, energy-dispersive X-ray spectroscopy, and electron microscopy techniques. The material was investment cast in a vacuum and then solution treated (1200 °C-2h) and aged (900 °C-8h). The γ matrix is mainly strengthened by the ordered L12 γ′ phase, with the mean γ/γ′ misfit, δ, +0.6%. The typical dendritic microstructure with considerable microsegregation of the alloying elements is revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…The STEM-EDX measurements showed that borides in the Rene´108 superalloy have significant amounts of W and Mo, which could increase their solvus temperature and consequently solidus temperature. [27] B. Influence of the Short-Term Annealing Temperature on the c/c¢ Misfit Coefficient…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The STEM-EDX measurements showed that borides in the Rene´108 superalloy have significant amounts of W and Mo, which could increase their solvus temperature and consequently solidus temperature. [27] B. Influence of the Short-Term Annealing Temperature on the c/c¢ Misfit Coefficient…”
Section: Resultsmentioning
confidence: 99%
“…Dendrite cores and arms consist of secondary and tertiary c¢ precipitates and (Cr, W) 5 B 3 nanoborides with a size around 50 nm at the c/c¢ interfaces. [27] In interdendritic regions, primary c¢ precipitates, (Ta, Hf)C carbides with various morphologies and M 23 C 6 nanocarbides, have additionally been detected. The M 23 C 6 nanocarbides form during aging, according to the phase transformation reaction MC + cfiM 23 C 6 + c¢.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The γ′ phase is the precipitation strengthened phase with a stoichiometric ration of Ni 3 Al. Al, Ti, Ta, Nb, and so on can be dissolved, which are named as γ′ phase elements [ 8 , 9 , 10 , 11 , 12 ]. With the rapid consumption of a large number of alloying element on the high-temperature environment, the original stable γ/γ′ structure will be destroyed [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Al, Ti, Ta, Nb, and so on can be dissolved, which are named as γ′ phase elements [ 8 , 9 , 10 , 11 , 12 ]. With the rapid consumption of a large number of alloying element on the high-temperature environment, the original stable γ/γ′ structure will be destroyed [ 10 , 11 ]. Therefore, the long-term service performance of the superalloy in harsh temperatures is often related to its composition components and constitute elements [ 12 ].…”
Section: Introductionmentioning
confidence: 99%